A Study on Self Regulation Techniques Training Towards Achievement of Students’ HRV - Muhammad Nubli, Abdul Wahab; Wan Rusyaini, Wan Mohd; Azham, Abdul Rahman (Foundation of Computer Science, 2015)
This experiment was about the implementation of self regulation techniques training in order to achieve the targeted HRV score. 20 secondary school students at the age of sixteen were chosen for this experiment. The students involved were known to have some behavioral problems. The experiment was to observe and study the importance of self regulation within the students in order to achieve the required HRV score. The students were taught and instructed to perform resonant breathing and dzikr recitation. Both were the self regulation techniques implemented for the experiment. A biofeedback device was used to monitor the changes in the students’ HRV as the experiment progressed. At the end of the experiment, it clearly showed the importance of self regulation in order to achieve the HRV score and thus changes in behaviors.